A prospective study examining elder-relevant outcomes in older adults with prostate cancer undergoing treatment with chemotherapy or abiraterone. Issue 2 (March 2016) - Manokumar, Tharsika; Aziz, Salman; Breunis, Henriette; Rizvi, S. Faraz; Joshua, Anthony M.; Tannock, Ian F.; Alibhai, Shabbir M.H.
Abstract: Background: Treatment of metastatic castration-resistant prostate cancer (mCRPC) with chemotherapy improves disease control and survival in fit older men (age 65 +) but its impact on function is not clear. We hypothesized that chemotherapy would impair daily function in older men with mCRPC. Methods: Men aged 65 + with mCRPC starting chemotherapy or abiraterone were enrolled in this prospective observational pilot study. Daily function was evaluated with the OARS Instrumental Activities of Daily Living (IADL) scale. Three objective measures were used to assess physical function. Patients completed Functional Assessment of Cancer Therapy questionnaires measuring prostate-specific and general quality-of-life (QOL). Vulnerability was evaluated using the Vulnerable Elders Survey (VES-13). Assessments were completed before each cycle of chemotherapy or every 2–3 months for those receiving abiraterone. We compared outcomes pre- and post-treatment and with published minimal clinically important differences. Results: We evaluated 29 and 7 men on 1st-line and 2nd-line chemotherapy (median 6 and 7 cycles, respectively) and 11 men receiving abiraterone for a median 7 months. IADL scores declined slightly after 1st-line chemotherapy (mean − 0.31 points, 95% confidence interval 0.39, − 1.02). Physical performance remained stable over time. Both general and prostate-specific QOL improved with 1st-line chemotherapy. For all but one outcome (Timed Chair Stands), vulnerable men had similar changes over time compared to non-vulnerable men. Second-line chemotherapy and abiraterone were generally well-tolerated. Conclusion: IADL function declined slightly whereas physical function remained stable and QOL improved during chemotherapy. Vulnerable and non-vulnerable older men with mCRPC appear to tolerate 1st-line chemotherapy fairly well.